Založnica pri Kamniku pod Krimom na Ljubljanskem barju - naselbina kulture Somogyvár-Vinkovci - Velušček, Anton (Arheološki vestnik, 2003)
The results are presented of archaeological and dendrochronological research at the site of Zaloznica near Kamnikpod Krimom in the Ljubljansko barje, Slovenia. The most significant settlement remains are related to the Somogyvár-Vinkovci Culture and are dated approximately to the 25th century BC.
Keywords: archaeology; arheologija; bakrena doba; dendrokronologija; Ljubljana Marshes; Ljubljansko barje; poselitev